Uji Aktivitas Antioksidan Ekstrak Etanol 70% Bunga Telang (Clitoria ternatea L) dari Daerah Sleman dengan Metode DPPH - Disa Andriani; Lusia Murtisiwi (Universitas Muhammadiyah Surakarta, 2020)
Telang flower (Clitoria ternatea L.) contains phenolic compounds which can act as antioxidants by donating hydrogen so as to stabilize the lack of electrons in free radicals. This study aims to determine the antioxidant potential of telang flower ethanol extract by looking at the IC50 value. Telang flowers were extracted by maceration method using 70% ethanol solvent. The potential for antioxidants was determined by the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with a comparison of vitamin C which had been shown to have the potential of free radicals which were very potent. The results showed the IC50 value of telang flower ethanol extract was 41.36 ± 1.191 μg / mL, based on that value the telang flower extract from the Sleman area was in the very potent category so that it could be developed as a source of antioxidants from natural ingredients.